DIGITIZATION OF JETIS BATIK MSME MARKETING AS A TRANSFORMATION OF LOCAL CULTURAL PRODUCTS - Wandira, Adellia Eka; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the digitalization of Jetis Batik MSME marketing as a transformation of local cultural products. Method: A qualitative descriptive approach was employed with data collection techniques including observation, documentation, and interviews, using purposive sampling to select informants based on specific objectives. The analysis applied Talcott Parsons’ AGIL framework to assess adaptation, goal achievement, and integration in the digitalization process. Results: The findings show that adaptation remains limited, as Jetis Batik MSME owners still rely on conventional systems and lack a dedicated online sales platform, though partial adjustments are made through reseller networks. Goal achievement is hindered by concerns over price disparities with resellers, preventing optimal realization of marketing targets. Meanwhile, integration has been relatively successful, as evidenced by coordination between owners and resellers and the implementation of training programs that support sustainability in digital marketing. Novelty: The study contributes originality by combining economic perspectives with cultural preservation, framing digitalization not merely as a marketing strategy but also as an effort to safeguard and promote Jetis Batik as a valuable element of local cultural heritage.